Association of plasma biomarkers, p-tau181, glial fibrillary acidic protein, and neurofilament light, with intermediate and long-term clinical Alzheimer's disease risk: results from a prospective cohort followed over 17 years - Stocker, Hannah; Beyer, Léon; Perna, Laura; Rujescu, Dan; Holleczek, Bernd; Beyreuther, Konrad; Stockmann, Julia; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann (Alzheimer's and dementia, 2023)
Blood biomarkers for Alzheimer's disease (AD) are the future of AD risk assessment. The aim of this study was to determine the association between plasma-measured phosphorylated tau (p-tau181), glial fibrillary acidic protein (GFAP), and neurofilament light (NfL) levels and risk of clinical AD incidence with consideration to the impact of cardiovascular health.
Online veröffentlicht: 02. März 2022
Gesehen am 09.03.2022